Green sustainable process for chemical and environmental engineering and science. - Inamuddin, 1980-; Altalhi, Tariq (Elsevier, 2023)
Green Sustainable Process for Chemical and Environmental Engineering and Science: Green Solvents and Extraction Technology provides information on the use of green solvents and their applications in the synthesis of pharmaceutical drugs, energy conversion and storage, catalysis, biodiesel synthesis, multicomponent reactions, waste valorization, and more. The book features introductory chapters related to the applications of green solvents and related extraction technology for sustainable development, including research trends, technical development, environment issues, and related concerns. The book provides examples covering the extraction of nanocellulose (from agricultural wastes), polysaccharides, phenolic compounds, antioxidants (from vegetables), biomolecules and green solvents (from biomass and precious metals).